A paper-based piezoelectric nanogenerator and a preparation method thereof

By using BCZT ceramic particles containing R phase and T phase in piezoelectric nanogenerators to prepare a two-layer composite film, the problems of low piezoelectric performance and limited application mode in the prior art are solved, and high-efficiency piezoelectric performance in various modes are achieved.

CN119401851BActive Publication Date: 2025-04-08XIAN SHUANGWANG ENG CONSULTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510012809.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing piezoelectric nanogenerators have limited application modes, low piezoelectric performance, and it is difficult to operate effectively in a variety of environments and modes.

Method used

Using the preparation method of paper-based piezoelectric nanogenerator, a two-layer composite film is prepared by adding BCZT ceramic particles containing R phase and T phase to the regenerated cellulose/PVDF mixed casting precursor solution, and the piezoelectric performance is improved through the casting and drying process.

Benefits of technology

The polarization strength and piezoelectric properties of piezoelectric nanogenerators are improved, allowing them to have higher output currents in d31 and d33 modes, expanding their application range and life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401851B_ABST
    Figure CN119401851B_ABST
Patent Text Reader

Abstract

The invention discloses a paper-based piezoelectric nanogenerator and a preparation method thereof, which belongs to the technical field of nanogenerators. First, BCZT ceramic particles with different crystal phases are prepared by a solid phase method, and then a layer of film and a two-layer composite film are cast by a method of layer-by-layer casting and adjusting the scraper height. Compared with a layer of film containing only one crystal phase, in a two-layer composite film containing two different crystal phases, the two crystal phase BCZT ceramic particles are co-doped, so that the piezoelectric nanogenerator has two working modes of d33 and d31. In the two-layer composite film, the three-dimensional hydrogen bond engineering strategy established between layers enables the two-layer composite film to have better mechanical properties. The combination of different working modes and higher mechanical properties enables the piezoelectric nanogenerator made of the two-layer composite film to be used in harsh mechanical environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanogenerators, and in particular relates to a paper-based piezoelectric nanogenerator and a preparation method thereof. Background Art

[0002] With the rapid increase in the consumption of traditional fossil energy, the development of alternative renewable energy has become the most important issue of concern to mankind. After decades of searching for renewable resources, wind power, hydropower, ocean energy, solar energy, etc. have been continuously developed, greatly supplementing the human demand for energy. However, traditional equipment for collecting and utilizing renewable energy usually requires huge infrastructure, large turbines and electromagnetic generators, and these devices are expensive, which makes it difficult to effectively collect and utilize small mechanical energy generated by breeze, water flow, and human limb movement. At the same time, miniaturized portable electronic devices and micro sensors usually require very low power and are much smaller than batteries. Nanogenerators can effectively collect micromechanical energy and convert it into electrical energy, which can not only serve as a substitute for traditional fossil energy to alleviate the serious problem of energy consumption, but also open up new areas.

[0003] Piezoelectric nanogenerators are mainly assembled from piezoelectric effect materials, such as piezoelectric ceramics such as lead zirconatetitanate (PZT) and barium titanate (BT), and piezoelectric polymers such as polyvinylidene fluoride (PVDF) and polyamide (PA). Devices made of traditional materials show excellent performance, but there are still some disadvantages, such as piezoelectric PZT contains heavy metal lead, poor biocompatibility, high price, and non-renewable, which limit the application of piezoelectric nanogenerators in some fields. Cellulose is the most abundant natural polymer on earth, with an annual global plant cellulose production of about 180 billion tons. Humans have a very long history of using cellulose, from ancient papermaking and weaving to the current application in the energy and electrical fields. Cellulose is used in all aspects of human society. In addition, cellulose has natural electrical insulation and was widely used as a paper capacitor in transformer systems in the last century. However, the piezoelectricity of cellulose itself is not strong, and if it is used alone to prepare nanogenerators, it is not enough to effectively collect energy. In addition, cellulose is hygroscopic. When placed in the air, a large number of water molecules will be produced inside it. If it is made into a piezoelectric nanogenerator, it cannot be used in a humid and watery environment. When used to collect energy from the human body, it is easily affected by body fluids, which greatly limits the application scope of the piezoelectric nanogenerator.

[0004] In view of the technical problem that the existing piezoelectric nanogenerators have limited application modes, it is urgent to find a new piezoelectric nanogenerator to enhance the piezoelectric performance of the piezoelectric nanogenerator so that it can operate in multiple modes. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a paper-based piezoelectric nanogenerator and a preparation method thereof, so as to solve the technical problem of limited application modes of piezoelectric nanogenerators in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing a paper-based piezoelectric nanogenerator, comprising the following steps:

[0008] 1) After the PVDF casting precursor solution and the regenerated cellulose solution are mixed and reacted, a regenerated cellulose / PVDF binary mixed casting precursor solution is obtained, which is divided into two equal parts, one part is added with BCZT ceramic particles containing R phase, and heated and stirred to obtain a first regenerated cellulose / PVDF-BCZT ternary casting precursor solution, and the other part is added with BCZT ceramic particles containing T phase, and heated and stirred to obtain a second regenerated cellulose / PVDF-BCZT ternary casting precursor solution;

[0009] 2) Casting the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution, leaving it to stand, to obtain a semi-dried wet film as the first layer of the membrane, and then casting the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution on the basis of the semi-dried wet film to obtain a second layer of the membrane, and after drying, ice water bath immersion, rinsing, and secondary drying, a two-layer composite membrane is obtained;

[0010] 3) After electrodes are attached to both sides of the two-layer composite film and connected with wires, a piezoelectric nanogenerator is obtained; after being encapsulated with a mixed solution, a paper-based piezoelectric nanogenerator is obtained.

[0011] Preferably, in step 1), the mass ratio of the PVDF casting precursor solution to the regenerated cellulose solution is 1:(5-7).

[0012] Preferably, in step 1), the BCZT ceramic particles containing R phase account for 1% of the mass of the regenerated cellulose / PVDF binary mixed casting precursor solution; the BCZT ceramic particles containing T phase account for 1% of the mass of the regenerated cellulose / PVDF binary mixed casting precursor solution.

[0013] Preferably, in step 1), BCZT ceramic particles containing R phase are prepared at high temperature, the high temperature firing temperature is 1200-1300°C, the firing time is 1-3h, and the particles are cooled with the furnace after firing, and the heating and cooling rates are both 2-5°C / min; BCZT ceramic particles containing T phase are prepared at low temperature, the low temperature firing temperature is 1000-1200°C, the firing time is 1-3h, and the particles are cooled with the furnace after firing, and the heating and cooling rates are both 2-5°C / min.

[0014] Preferably, in step 1), the preparation method of the regenerated cellulose solution comprises: adding cotton linters to a DMAC solution and soaking for 48-72 hours, wherein the mass ratio of cotton linters to DMAC solution is 1:(25-35), stirring at 160-180°C for 25-30 minutes, taking out the cotton linters when the temperature drops to 70-80°C, squeezing out the DMAC solution, transferring to an environment of 80-100°C for drying, and obtaining cotton linters cellulose; then adding the mixture to a DMAC / LiCl mixed solution, stirring at 90-110°C for 3-5 hours, then stirring at room temperature for 24-30 hours, standing for not less than 48 hours, and centrifuging at a speed of 5000-5800 r / min to obtain a regenerated cellulose solution.

[0015] Preferably, in step 1), the method for preparing the PVDF casting precursor solution comprises: adding PVDF powder and LiCl to a DMAC solution, stirring at 50°C-70°C for 2-3h to obtain a PVDF casting precursor solution; the mass ratio of PVDF powder, LiCl and DMAC solution is (1-3): (1-1.4): (15-20).

[0016] Preferably, in step 1), the mixing reaction conditions are: multiple ultrasonic stirring, and then continued stirring reaction; the stirring reaction time is 10-12 hours; the heating stirring conditions are: heating stirring at 70-80° C. for 30-50 minutes.

[0017] Preferably, in step 2), the casting conditions of the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution are: casting on a glass plate at a speed of 12-15 cm / min to a thickness of 10-13 μm; the placement time is 6-8 hours; the casting conditions of the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution are: casting on a semi-dried wet film at a speed of 12-15 cm / min to a thickness of 23-26 μm;

[0018] The drying conditions are: drying at 25-30°C for 12-15 hours; the soaking time in an ice water bath is: 60-80 minutes; the rinsing conditions are: rinsing in running tap water for 12-15 hours; the secondary drying conditions are: secondary drying at 60-80°C for 6-8 hours.

[0019] Preferably, in step 3), the mixed solution is obtained by mixing polydimethylsiloxane and a curing agent in a mass ratio of (9-11):1 and then vacuuming; the vacuuming conditions are: a vacuum degree of 0.8-1.0 MPa, and a vacuuming time of 20-30 min.

[0020] In a second aspect, the present invention further discloses a paper-based piezoelectric nanogenerator, which is prepared by the preparation method of the paper-based piezoelectric nanogenerator.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention discloses a method for preparing a paper-based piezoelectric nanogenerator, wherein BCZT ceramic particles containing an R phase are added to a regenerated cellulose / PVDF binary mixed casting precursor solution, the first layer of a two-layer composite film is cast, and the film is left to stand to form a semi-dried wet film, and then BCZT ceramic particles containing a T phase are added to the regenerated cellulose / PVDF binary mixed casting precursor solution, the second layer of the two-layer composite film is cast, and the film is completely dried to form a two-layer composite film. The two-layer composite film is prepared by adding BCZT ceramic particles containing different crystal phases, the BCZT ceramic particles containing the T phase enable the piezoelectric nanogenerator to have a higher output in the d33 mode, and the BCZT ceramic particles containing the R phase enable the piezoelectric nanogenerator to have a higher output in the d31 mode. These multiple changing factors further improve the polarization strength and piezoelectric performance of the final nanogenerator, and by adding a variety of crystal phase ceramics and adding different crystal phase ceramics to different layer structures of the composite film, the problem of low polarization and piezoelectric performance of the existing cellulose-based piezoelectric film is solved. A two-layer composite film was prepared by casting layer by layer and adjusting the scraper height. Two BCZT ceramic particles with high piezoelectric properties of different crystal phases were added to the prepared two-layer composite film, which further improved the performance of the piezoelectric nanogenerator. A higher electrical signal output was observed during the piezoelectric performance test. The piezoelectric nanogenerator was encapsulated by protective materials to reduce the impact of the use environment on the piezoelectric nanogenerator, thereby expanding the use range and life of the piezoelectric nanogenerator.

[0023] Furthermore, calcium barium zirconate titanate (0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3TiO2, BCZT) ceramic particles, and it was verified that the BCZT ceramic particles obtained by the solid phase method have almost no impurities; the BCZT ceramic particles are well developed, small in size, evenly distributed, light in particle agglomeration, low in raw material cost, and simple in process. The solid phase method is used to sinter BCZT ceramic particles with different crystal phases at a specific temperature; adding BCZT ceramic particles containing different crystal phases allows the piezoelectric nanogenerator to work in multiple modes, thereby increasing the piezoelectric performance of the piezoelectric nanogenerator.

[0024] Furthermore, by adopting a two-layer structure, the regenerated cellulose-based film can be made flat and defect-free while the thickness of each functional layer can be precisely controlled.

[0025] Furthermore, polydimethylsiloxane (PDMS) packaging material is used, and polydimethylsiloxane and curing agent are mixed in a mass ratio of (9-11):1. After fusion, vacuum is drawn to remove bubbles to avoid affecting the performance of the piezoelectric nanogenerator. After the packaging material is prepared, it is poured on the surface of the two-layer composite film to form a protective layer of a certain uniform thickness around the two-layer composite film. After the protective layer is dried, a simple paper-based piezoelectric nanogenerator is obtained.

[0026] Furthermore, the speed of 12-15 cm / min ensures that the casting is not too fast, resulting in uneven casting, or too slow, resulting in the film absorbing moisture during the casting process, thereby affecting the performance of the piezoelectric nanogenerator.

[0027] The present invention discloses a paper-based piezoelectric nanogenerator. The paper-based piezoelectric nanogenerator is small in size and low in cost. It has BCZT ceramic particles of different crystal phases with high piezoelectric performance. While enhancing the performance of the nanogenerator, the paper-based piezoelectric nanogenerator can be used in multiple modes. PVDF not only has a piezoelectric effect but also ensures that the two-layer composite film will not curl. By encapsulating the two-layer composite film in a protective material, the problem of high water absorption of the internal cellulose is solved. At the same time, the internal two-layer composite film can be protected from external pollution, and the piezoelectric signal can be output stably and continuously, which broadens the scope of use of the piezoelectric nanogenerator. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagrams of the structures of a single-layer film-R prepared in Comparative Example 1 of the present invention, a single-layer film-T prepared in Comparative Example 2, and a double-layer composite film-R / T prepared in Example 1; wherein (a1) is a schematic diagram of a single-layer film-R; (a2) is a schematic diagram of a single-layer film-T; (a3) ​​is a schematic diagram of a double-layer composite film-R / T;

[0029] Figure 2XRD refined images of BCZT ceramic particles containing R phase and BCZT ceramic particles containing T phase prepared in Example 1 of the present invention; wherein (a1) is BCZT ceramic particles containing R phase; (a2) is BCZT ceramic particles containing T phase;

[0030] Figure 3 are the short-circuit currents of different membranes measured in different modes; wherein, (a1) is a schematic diagram of the measurement of the piezoelectric nanogenerator-R in the d33 mode; (a2) is a schematic diagram of the measurement of the piezoelectric nanogenerator-R in the d31 mode; (b1) is the output current of the piezoelectric nanogenerator-R prepared in comparative example 1 in the d31 mode; (b2) is the output current of the piezoelectric nanogenerator-R prepared in comparative example 1 in the d33 mode; (c1) is the output current of the piezoelectric nanogenerator-T prepared in comparative example 2 in the d31 mode; (c2) is the output current of the piezoelectric nanogenerator-T prepared in comparative example 2 in the d33 mode; (d1) is the output current of the paper-based piezoelectric nanogenerator-R / T prepared in Example 1 in the d31 mode; (d2) is the output current of the paper-based piezoelectric nanogenerator-R / T prepared in Example 1 in the d33 mode;

[0031] Figure 4 The stress-strain curves and Young's modulus diagrams of a layer of film R prepared in comparative example 1, a layer of film T prepared in comparative example 2, and a two-layer composite film R / T prepared in example 1 under the same external force conditions; wherein (a1) is the stress-strain curve diagram; and (a2) is the Young's modulus diagram. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0033] It should be noted that the terms "first", "second", etc. of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product, or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products, or devices.

[0034] The present invention discloses a method for preparing a paper-based piezoelectric nanogenerator, comprising the following steps:

[0035] Step 1: Preparation of BCZT ceramic nanoparticle filler by solid phase method

[0036] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3 The molar ratio in TiO2 is 11.4414g BaCO3, 2.1464g CaCO3, 0.1957g ZrO3 and 6.2164g TiO3. The weighed raw materials are placed in a ball mill, the ball milling medium is added, the ball mill is started after the ball mill is closed for 10-12h to ensure sufficient mixing and refinement, then the ball mill is stopped, the mixed powder is taken out, and the larger or agglomerated particles are removed by sieving to ensure that the mixed particles are of uniform size to obtain the powder to be fired.

[0037] 2) Divide the powder to be fired into two parts, place them in a crucible for low-temperature firing and high-temperature firing respectively; the temperature of low-temperature firing is 1000-1200℃, the firing time is 1-3h, and the furnace is cooled after firing, and the heating and cooling rates are both 2-5℃ / min, to obtain low-temperature fired powder, BCZT ceramic particles containing T phase; the temperature of high-temperature firing is 1200-1300℃, the firing time is 1-3h, and the furnace is cooled after firing, and the heating and cooling rates are both 2-5℃ / min, to obtain high-temperature fired powder, BCZT ceramic particles containing R phase.

[0038] Step 2: Preparation of regenerated cellulose solution

[0039] 3) Add cotton linters to a flask containing N,N-dimethylacetamide (DMAC) solution and soak for 48-72 hours. The mass ratio of cotton linters to DMAC solution is 1: (25-35). After soaking, transfer to an oil bath-magnetic stirrer and stir at 160-180℃ for 25-30min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask drops to 70-80℃, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and transfer to 80-100℃ to dry and remove the remaining DMAC solution to obtain cotton linters cellulose.

[0040] 4) adding 1-3 g of the cotton linter cellulose obtained in step 3) to 50-70 g of a DMAC / LiCl mixed solution, stirring at 90-110° C. for 3-5 h, and then stirring at room temperature for 24-30 h to obtain a regenerated cellulose casting precursor solution, and then leaving the flask to stand to precipitate impurities in the regenerated cellulose solution; the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:(9-11).

[0041] 5) Pour the regenerated cellulose solution that has been standing for no less than 48 hours into a centrifuge tube, and separate the impurities from the regenerated cellulose solution at a centrifugal speed of 5000-5800 r / min. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0042] Step 3: Preparation of PVDF casting precursor solution

[0043] 6) Add 1-3 g PVDF powder and 1-1.4 g LiCl to 15-20 g DMAC solution, preferably, the mass ratio of LiCl to DMAC solution is 1:(14-16), and stir at 50-70° C. for 2-3 h to obtain a PVDF casting precursor solution.

[0044] Step 4: Preparation of ternary casting precursor solution

[0045] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) are mixed in a mass ratio of 1: (5-7), ultrasonicated for 30-50 minutes, stirred for 30-50 minutes, and then cycled for 5-7 times, and finally transferred to a magnetic stirrer for continued stirring and reaction for 10-12 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; the regenerated cellulose / PVDF binary mixed casting precursor solution is divided into two equal parts, and then BCZT ceramic particles containing R phase and BCZT ceramic particles containing T phase are added respectively to obtain two ternary mixed solutions. Solution-1: 1wt% of BCZT ceramic particles containing R phase are added; Solution-2: 1wt% of BCZT ceramic particles containing T phase are added.

[0046] Subsequently, the two ternary mixed solutions were ultrasonicated at room temperature for 1 hour, and then heated and stirred at 70-80°C for 30-50 minutes to obtain two regenerated cellulose / PVDF-BCZT ternary casting precursor solutions; the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution and the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0047] Step 5: Preparation of cellulose-based composite materials

[0048] 8) The first regenerated cellulose / PVDF-BCZT ternary casting precursor solution is cast on a glass plate at a casting rate of 12-15cm / min to a thickness of 10-13μm, and placed for 6-8h to obtain a semi-dried wet film, that is, the first layer of the two-layer composite film, and then the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution is adjusted by the scraper, and a second film of 23-26μm is cast on the basis of the semi-dried wet film at a speed of 12-15cm / min, that is, the second layer of the two-layer composite film is obtained. After the end, it is placed in a closed oven at a temperature of 25-30℃ and dried for 12-15h. After complete drying, the two-layer composite film to be treated -R / T is obtained.

[0049] In the above-mentioned casting process, the timing of casting each layer needs to be precisely controlled, and the casting is carried out when the previous layer is formed and not completely dried. If the drying time of the previous layer is too short, the next layer is cast, which easily causes the previous layer to be scraped off. If the previous layer is already dry, the next layer is cast, so that the three-dimensional hydrogen bond network structure cannot be formed between the two in the subsequent drying process, thereby failing to improve the mechanical properties of the two-layer composite film.

[0050] 9) The two-layer composite membrane-R / T to be treated obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 60-80 minutes, then transferred to running tap water for rinsing for 12-15 hours, and then transferred to an electric heated blast drying oven for secondary drying at 60-80°C for 6-8 hours. After the secondary drying is completed, a two-layer composite membrane-R / T is obtained.

[0051] Step 6: Prepare the piezoelectric nanogenerator

[0052] 10) Cut a circular film with a radius of 1.3-1.6 cm from the two-layer composite film -R / T in step 9), then cut out two copper electrodes with a radius of 1.0-1.2 cm, and cut two wires with a length of 10-12 cm. Remove 1.0-1.2 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then bond them to the two copper electrodes, and then bond them to both sides of the circular film in a completely aligned manner. After bonding, a piezoelectric nanogenerator is obtained.

[0053] Step 7: Prepare the encapsulation mixture

[0054] 11) Mix the main agent and the curing agent and stir for 10-30 minutes, the mass ratio of the main agent: curing agent = (9-11): 1, and evacuate in a vacuum drying oven for 20-30 minutes to remove bubbles generated during stirring in the mixed solution, the vacuum degree is 0.8-1.0MPa, and then obtain a mixed solution for encapsulating piezoelectric nanogenerators. Among them, the main agent is polydimethylsiloxane and the curing agent is diphenylbutyl carbamate.

[0055] Step 8: Encapsulate the Piezoelectric Nanogenerator

[0056] 12) Pour the mixed solution in step 11) into clean containers of 5cm×5cm×5cm respectively. After pouring the mixed solution to a height of 0.5-1mm, place a two-layer composite film-R / T close to the liquid surface in the container and fix it. Then pour the mixed solution to a height of 0.5-1mm into the container to cover the surface of the film. After that, put it in a closed drying oven at 60-80℃ and dry it for 2-4h to obtain the encapsulated piezoelectric nanogenerator, paper-based piezoelectric nanogenerator-R / T.

[0057] Example 1

[0058] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0059] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3The molar ratio in TiO2 is 11.4414g BaCO3, 2.1464g CaCO3, 0.1957g ZrO3 and 6.2164g TiO3. The weighed raw materials are placed in a ball mill, the ball mill medium is added, the ball mill is started after the ball mill is sealed and mixed for 10 hours, and the powder to be fired is obtained by sieving.

[0060] 2) The powder to be fired is divided into two parts, and placed in a crucible for low-temperature firing and high-temperature firing respectively; the temperature of low-temperature firing is 1100°C, the firing time is 2h, and the furnace is cooled after firing, and the heating and cooling rates are both 2°C / min, to obtain BCZT ceramic particles containing T phase; the temperature of high-temperature firing is 1250°C, the firing time is 2h, and the furnace is cooled after firing, and the heating and cooling rates are both 2°C / min, to obtain BCZT ceramic particles containing R phase.

[0061] 3) Add cotton linters to a flask containing DMAC solution and soak for 48 hours. The mass ratio of cotton linters to DMAC solution is 1:30. After soaking, transfer to an oil bath-magnetic stirrer and stir at 160°C for 30 minutes. When the temperature in the flask drops to 80°C, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 100°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0062] 4) adding 2 g of the cotton linter cellulose obtained in step 3) to 60 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:10; stirring at 100° C. for 5 h, and then stirring at room temperature for 24 h, to obtain a regenerated cellulose casting precursor solution;

[0063] 5) The regenerated cellulose casting precursor solution is allowed to stand for 48 hours, and the impurities and the regenerated cellulose solution are separated at a centrifugal speed of 5000 r / min. After the centrifugation, the upper clear and transparent solution without impurities is collected to obtain the regenerated cellulose solution, which is sealed and stored.

[0064] 6) Add 2 g PVDF powder and 1.2 g LiCl to 18 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:15, and stir at 50 °C for 2 h to obtain a PVDF casting precursor solution.

[0065] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:6, ultrasonicated for 30 minutes, stirred for 30 minutes, and repeated for 5 times, and finally transferred to a magnetic stirrer and stirred for 12 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; the regenerated cellulose / PVDF binary mixed casting precursor solution was divided into two parts, one of which was added with 1wt% of BCZT ceramic particles containing R phase to obtain solution-1; the other part was added with 1wt% of BCZT ceramic particles containing T phase to obtain solution-2. Subsequently, the two ternary mixed solutions were ultrasonicated at room temperature for 1 hour, and then stirred at 70°C for 30 minutes to obtain two regenerated cellulose / PVDF-BCZT ternary casting precursor solutions, the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution and the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0066] 8) The first regenerated cellulose / PVDF-BCZT ternary casting precursor solution was cast on a glass plate at a speed of 15 cm / min to a thickness of 12.5 μm, and left for 8 hours to obtain a semi-dried wet film, that is, the first layer of the two-layer composite film was obtained. Then, the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution was adjusted by the scraper, and a second layer of 25 μm was cast on the semi-dried wet film at a speed of 15 cm / min, that is, the second layer of the two-layer composite film was obtained. After the end, it was placed in a closed oven at a temperature of 25°C and dried for 12 hours. After complete drying, a two-layer composite film was obtained, named two-layer composite film-R / T.

[0067] 9) The two-layer composite membrane-R / T obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 60 minutes, then transferred to running tap water and kept for 12 hours, and then transferred to an electric heated blast drying oven and dried at 80°C for 8 hours. After drying, a two-layer composite membrane-R / T is obtained.

[0068] 10) Cut a circular film with a radius of 1.5 cm from the two-layer composite film-R / T in step 9), then cut out two copper electrodes with a radius of 1.2 cm, and cut two wires with a length of 10 cm. Remove 1 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then stick them on the two copper electrodes, and then stick them on both sides of the circular film in a completely aligned manner. After the bonding is completed, a piezoelectric nanogenerator is obtained.

[0069] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 10:1 for 10 minutes, and the mixture was evacuated in a vacuum drying oven for 30 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 0.8 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0070] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After pouring the mixed solution to a height of 1mm, place a two-layer composite film -R / T close to the liquid surface in the container and fix it. Then pour the mixed solution to a height of 1mm into the container to cover the surface of the film. After that, put it in a closed drying oven and dry it at 80℃ for 2h to obtain a paper-based piezoelectric nanogenerator -R / T.

[0071] Example 2

[0072] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0073] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3 The molar ratio in TiO2 is 11.4414g BaCO3, 2.1464g CaCO3, 0.1957g ZrO3 and 6.2164g TiO3. The weighed raw materials are placed in a ball mill, the ball mill medium is added, the ball mill is started after the ball mill is sealed, and the mixing is carried out for 12 hours, and the powder to be fired is obtained by sieving.

[0074] 2) The powder to be fired is divided into two parts, and placed in a crucible for low-temperature firing and high-temperature firing respectively; the low-temperature firing temperature is 1050°C, the firing time is 1.5h, and the furnace is cooled after firing, and the heating and cooling rates are both 3°C / min, to obtain BCZT ceramic particles containing T phase; the high-temperature firing temperature is 1250°C, the firing time is 1.5h, and the furnace is cooled after firing, and the heating and cooling rates are both 3°C / min, to obtain BCZT ceramic particles containing R phase.

[0075] 3) Add cotton linters to a flask containing DMAC solution and soak for 72 hours. The mass ratio of cotton linters to DMAC solution is 1:30. After soaking, transfer to an oil bath-magnetic stirrer and stir at 165°C for 28 minutes. When the temperature in the flask drops to 78°C, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 95°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0076] 4) adding 2 g of the cotton linter cellulose obtained in step 3) to 50 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:10; stirring at 90° C. for 4 h, and then stirring at room temperature for 26 h, to obtain a regenerated cellulose casting precursor solution;

[0077] 5) The regenerated cellulose casting precursor solution was allowed to stand for 54 hours, and the impurities were separated from the regenerated cellulose solution at a centrifugal speed of 5800 r / min. After the centrifugation, the upper clear and transparent solution without impurities was collected to obtain the regenerated cellulose solution, which was sealed and stored.

[0078] 6) Add 1 g PVDF powder and 1 g LiCl to 15 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:15, and stir at 55 °C for 3 h to obtain a PVDF casting precursor solution.

[0079] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:5, ultrasonicated for 40 minutes, stirred for 40 minutes, and repeated 7 times, and finally transferred to a magnetic stirrer and stirred for 10 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; the regenerated cellulose / PVDF binary mixed casting precursor solution was divided into two parts, and 1wt% of BCZT ceramic particles containing R phase were added to one part to obtain solution-1; 1wt% of BCZT ceramic particles containing T phase were added to the other part to obtain solution-2. Subsequently, the two ternary mixed solutions were ultrasonicated at room temperature for 1 hour, and then stirred at 80°C for 50 minutes to obtain two regenerated cellulose / PVDF-BCZT ternary casting precursor solutions, the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution and the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0080] 8) The first regenerated cellulose / PVDF-BCZT ternary casting precursor solution was cast on a glass plate at a speed of 14 cm / min to a thickness of 10 μm, and left for 6 hours to obtain a semi-dried wet film, that is, the first layer of the two-layer composite film was obtained. Then, the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution was adjusted by the scraper, and a second film of 23 μm was cast on the semi-dried wet film at a speed of 14 cm / min, that is, the second layer of the two-layer composite film was obtained. After the end, it was placed in a closed oven at a temperature of 26°C and dried for 13 hours. After complete drying, a two-layer composite film was obtained, which was named two-layer composite film-R / T.

[0081] 9) The two-layer composite membrane-R / T obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 70 minutes, then transferred to running tap water and kept for 13 hours, and then transferred to an electric heated blast drying oven and dried at 70°C for 6 hours. After drying, a two-layer composite membrane-R / T is obtained.

[0082] 10) Cut a circular film with a radius of 1.3 cm from the two-layer composite film-R / T in step 9), then cut out two copper electrodes with a radius of 1.0 cm, and cut off two wires with a length of 11 cm. Remove 1.1 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then bond them to the two copper electrodes, and then bond them to both sides of the circular film in a completely aligned manner. After bonding, a piezoelectric nanogenerator is obtained.

[0083] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 9:1 for 25 minutes, and the mixture was evacuated in a vacuum drying oven for 25 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 1.0 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0084] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After the mixed solution is poured to a height of 0.5mm, place a two-layer composite film -R / T close to the liquid surface in the container and fix it. Then pour 0.5mm high of the mixed solution into the container to cover the surface of the film. After completion, put it in a closed drying oven at 70°C and dry it for 4 hours to obtain a paper-based piezoelectric nanogenerator -R / T.

[0085] Example 3

[0086] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0087] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3 The molar ratio in TiO2 is 11.4414g BaCO3, 2.1464g CaCO3, 0.1957g ZrO3 and 6.2164g TiO3. The weighed raw materials are placed in a ball mill, the ball milling medium is added, the ball mill is started after the ball mill is sealed, and the mixing is carried out for 11 hours, and the powder to be fired is obtained by sieving.

[0088] 2) The powder to be fired is divided into two parts, and placed in a crucible for low-temperature firing and high-temperature firing respectively; the low-temperature firing temperature is 1000°C, the firing time is 3 hours, and the furnace is cooled after firing, and the heating and cooling rates are both 4°C / min, to obtain BCZT ceramic particles containing T phase; the high-temperature firing temperature is 1200°C, the firing time is 3 hours, and the furnace is cooled after firing, and the heating and cooling rates are both 4°C / min, to obtain BCZT ceramic particles containing R phase.

[0089] 3) Add cotton linter to a flask containing DMAC solution and soak for 60 hours. The mass ratio of cotton linter to DMAC solution is 1:25. After soaking, transfer to an oil bath-magnetic stirrer and stir at 170°C for 27 minutes. When the temperature in the flask drops to 74°C, take out the cotton linter, move the cotton linter to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 90°C for drying, remove the remaining DMAC solution, and obtain cotton linter cellulose.

[0090] 4) adding 1 g of the cotton linter cellulose obtained in step 3) to 50 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:9; stirring at 110° C. for 3.5 h, and then stirring at room temperature for 28 h, to obtain a regenerated cellulose casting precursor solution;

[0091] 5) The regenerated cellulose casting precursor solution was allowed to stand for 52 hours, and the impurities were separated from the regenerated cellulose solution at a centrifugal speed of 5600 r / min. After the centrifugation, the upper clear and transparent solution without impurities was collected to obtain the regenerated cellulose solution, which was sealed and stored.

[0092] 6) 3 g PVDF powder and 1.3 g LiCl were added to 16 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:16, and stirred at 60 °C for 2.5 h to obtain a PVDF casting precursor solution.

[0093] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:7, ultrasonicated for 50 minutes, and then stirred for 50 minutes, and this cycle was repeated 6 times, and finally transferred to a magnetic stirrer and continued to stir for 11 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; the regenerated cellulose / PVDF binary mixed casting precursor solution was divided into two parts, and 1wt% of BCZT ceramic particles containing R phase were added to one part to obtain solution-1; 1wt% of BCZT ceramic particles containing T phase were added to the other part to obtain solution-2. Subsequently, the two ternary mixed solutions were ultrasonicated at room temperature for 1 hour, and then stirred at 75°C for 40 minutes to obtain two regenerated cellulose / PVDF-BCZT ternary casting precursor solutions, the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution and the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0094] 8) The first regenerated cellulose / PVDF-BCZT ternary casting precursor solution was cast on a glass plate at a speed of 13 cm / min to a thickness of 11 μm, and left for 7 hours to obtain a semi-dried wet film, that is, the first layer of the two-layer composite film was obtained. Then, the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution was adjusted by the scraper, and a second film of 24 μm was cast on the semi-dried wet film at a speed of 13 cm / min, that is, the second layer of the two-layer composite film was obtained. After the end, it was placed in a closed oven at a temperature of 27°C and dried for 14 hours. After complete drying, a two-layer composite film was obtained, which was named two-layer composite film-R / T.

[0095] 9) The two-layer composite membrane-R / T obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 80 minutes, then transferred to running tap water and kept for 14 hours, and then transferred to an electric heated blast drying oven and dried at 60°C for 8 hours. After drying, a two-layer composite membrane-R / T is obtained.

[0096] 10) Cut a circular film with a radius of 1.6 cm from the two-layer composite film-R / T in step 9), then cut out two copper electrodes with a radius of 1.1 cm, and cut two wires with a length of 12 cm. Remove 1.2 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then bond them to the two copper electrodes, and then bond them to both sides of the circular film in a completely aligned manner. After bonding, a piezoelectric nanogenerator is obtained.

[0097] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 11:1 for 30 minutes, and the mixture was evacuated in a vacuum drying oven for 20 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 0.9 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0098] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After the mixed solution is poured to a height of 0.9mm, place a two-layer composite film -R / T close to the liquid surface in the container and fix it. Then pour the mixed solution to a height of 0.9mm into the container to cover the surface of the film. After completion, put it in a closed drying oven at 60°C and dry it for 3h to obtain a paper-based piezoelectric nanogenerator -R / T.

[0099] Example 4

[0100] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0101] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3The molar ratio in TiO2 is 11.4414g BaCO3, 2.1464g CaCO3, 0.1957g ZrO3 and 6.2164g TiO3. The weighed raw materials are placed in a ball mill, the ball milling medium is added, the ball mill is started after the ball mill is sealed, and the mixing is carried out for 10 hours, and the powder to be fired is obtained by sieving.

[0102] 2) The powder to be fired is divided into two parts, and placed in a crucible for low-temperature firing and high-temperature firing respectively; the low-temperature firing temperature is 1200°C, the firing time is 1 hour, and the furnace is cooled after firing, and the heating and cooling rates are both 5°C / min, to obtain BCZT ceramic particles containing T phase; the high-temperature firing temperature is 1300°C, the firing time is 1 hour, and the furnace is cooled after firing, and the heating and cooling rates are both 5°C / min, to obtain BCZT ceramic particles containing R phase.

[0103] 3) Add cotton linters to a flask containing DMAC solution and soak for 48 hours. The mass ratio of cotton linters to DMAC solution is 1:35. After soaking, transfer to an oil bath-magnetic stirrer and stir at 180°C for 25 minutes. When the temperature in the flask drops to 70°C, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 80°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0104] 4) adding 3 g of the cotton linter cellulose obtained in step 3) to 70 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to the DMAC solution in the DMAC / LiCl mixed solution is 1:11; stirring at 100° C. for 3 h, and then stirring at room temperature for 30 h, to obtain a regenerated cellulose casting precursor solution;

[0105] 5) The regenerated cellulose casting precursor solution was allowed to stand for 50 hours, and the impurities and the regenerated cellulose solution were separated at a centrifugal speed of 5400 r / min. After the centrifugation, the upper clear and transparent solution without impurities was collected to obtain the regenerated cellulose solution, which was sealed and stored.

[0106] 6) Add 1 g PVDF powder and 1.4 g LiCl to 20 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:14, and stir at 70 °C for 2 h to obtain a PVDF casting precursor solution.

[0107] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:6, ultrasonicated for 40 minutes, stirred for 40 minutes, and repeated for 5 times, and finally transferred to a magnetic stirrer and stirred for 12 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; the regenerated cellulose / PVDF binary mixed casting precursor solution was divided into two parts, and 1wt% of BCZT ceramic particles containing R phase were added to one part to obtain solution-1; 1wt% of BCZT ceramic particles containing T phase were added to the other part to obtain solution-2. Subsequently, the two ternary mixed solutions were ultrasonicated at room temperature for 1 hour, and then stirred at 70°C for 30 minutes to obtain two regenerated cellulose / PVDF-BCZT ternary casting precursor solutions, the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution and the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0108] 8) The first regenerated cellulose / PVDF-BCZT ternary casting precursor solution was cast on a glass plate at a speed of 12 cm / min to a thickness of 13 μm, and left for 8 hours to obtain a semi-dried wet film, that is, the first layer of the two-layer composite film was obtained. Then, the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution was adjusted by the scraper, and a second layer of 26 μm was cast on the semi-dried wet film at a speed of 12 cm / min, that is, the second layer of the two-layer composite film was obtained. After the end, it was placed in a closed oven at a temperature of 30°C and dried for 15 hours. After complete drying, a two-layer composite film was obtained, named two-layer composite film-R / T.

[0109] 9) The two-layer composite membrane-R / T obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 60 minutes, then transferred to running tap water and kept for 15 hours, and then transferred to an electric heated blast drying oven and dried at 75°C for 7 hours. After drying, a two-layer composite membrane-R / T is obtained.

[0110] 10) Cut a circular film with a radius of 1.4 cm from the two-layer composite film-R / T in step 9), then cut out two copper electrodes with a radius of 1.2 cm, and cut two wires with a length of 10 cm. Remove 1 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then stick them on the two copper electrodes, and then stick them on both sides of the circular film in a completely aligned manner. After the bonding is completed, a piezoelectric nanogenerator is obtained.

[0111] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 10:1 for 15 minutes, and the mixture was evacuated in a vacuum drying oven for 30 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 0.8 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0112] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After the mixed solution is poured to a height of 0.7mm, place a two-layer composite film -R / T close to the liquid surface in the container and fix it. Then pour the mixed solution to a height of 0.7mm into the container to cover the surface of the film. After completion, put it in a closed drying oven at 75°C and dry it for 2.5h to obtain a paper-based piezoelectric nanogenerator -R / T.

[0113] Comparative Example 1

[0114] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0115] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3 The molar ratio in TiO2 is 11.4414gBaCO3, 2.1464gCaCO3, 0.1957gZrO3 and 6.2164gTiO3. The weighed raw materials are placed in a ball mill, the ball milling medium is added, the ball mill is started after the ball mill is sealed, and the mixing is carried out for 10 hours, and the powder to be fired is obtained by sieving.

[0116] 2) The powders to be fired are placed in crucibles for high-temperature firing; the high-temperature firing temperature is 1250°C, the firing time is 2 hours, and the powders are cooled with the furnace after firing. The heating and cooling rates are both 2°C / min to obtain BCZT ceramic particles containing R phase.

[0117] 3) Add cotton linters to a flask containing DMAC solution and soak for 48 hours. The mass ratio of cotton linters to DMAC solution is 1:30. After soaking, transfer to an oil bath-magnetic stirrer and stir at 160°C for 30 minutes. When the temperature in the flask drops to 80°C, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 100°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0118] 4) adding 2 g of the cotton linter cellulose obtained in step 3) to 60 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:10; stirring at 100° C. for 5 h, and then stirring at room temperature for 24 h, to obtain a regenerated cellulose casting precursor solution;

[0119] 5) The regenerated cellulose casting precursor solution is allowed to stand for 48 hours, and the impurities and the regenerated cellulose solution are separated at a centrifugal speed of 5000 r / min. After the centrifugation, the upper clear and transparent solution without impurities is collected to obtain the regenerated cellulose solution, which is sealed and stored.

[0120] 6) Add 2 g PVDF powder and 1.2 g LiCl to 18 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:15, and stir at 50 °C for 2 h to obtain a PVDF casting precursor solution.

[0121] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:6, ultrasonicated for 30 minutes, stirred for 30 minutes, and cycled for 5 times, and finally transferred to a magnetic stirrer and stirred for 12 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; 2wt% of R-phase BCZT was added to the regenerated cellulose / PVDF binary mixed casting precursor solution to obtain solution-3. After ultrasonication at room temperature for 1 hour, the solution was stirred at 70°C for 30 minutes to obtain a third regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0122] 8) The third regenerated cellulose / PVDF-BCZT ternary casting precursor solution obtained in step 7) is injected into the guide plate of the adjustable scraper, the scraper height is adjusted to 25m, and the casting is carried out on a clean glass plate at a speed of 15cm / min. After completion, it is placed in a closed oven at a temperature of 25°C and dried for 12 hours. After complete drying, a layer of membrane-R is obtained.

[0123] 9) The film-R obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 60 minutes, and then the film is transferred to running tap water for 12 hours. The washed film is then transferred to an electric hot air drying oven and dried at 80°C for 8 hours, and a film-R is obtained after drying.

[0124] 10) Cut a circular film with a radius of 1.5 cm from the composite film in step 9), then cut out two copper electrodes with a radius of 1.2 cm, and then cut two wires with a length of 10 cm. Remove 1 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then stick them on the two copper electrodes, and then stick them on both sides of the circular film in a completely aligned manner. After the bonding is completed, a piezoelectric nanogenerator is obtained.

[0125] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 10:1 for 10 minutes, and the mixture was evacuated in a vacuum drying oven for 30 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 0.8 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0126] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After pouring the mixed solution to a height of 1mm, place a layer of membrane-R close to the surface of the liquid in the container and fix it. Then pour 1mm of the mixed solution into the container to cover the surface of the membrane. After that, put it in a closed drying oven and dry it at 80℃ for 2h to obtain the encapsulated piezoelectric nanogenerator-R.

[0127] Comparative Example 2

[0128] A method for preparing a paper-based piezoelectric nanogenerator comprises the following steps:

[0129] 1) First, according to the chemical formula 0.1BaZr 0.2 Ti 0.8 O3-0.9Ba 0.7 Ca 0.3 The molar ratio in TiO2 is 11.4414gBaCO3, 2.1464gCaCO3, 0.1957gZrO3 and 6.2164gTiO3. The weighed raw materials are placed in a ball mill, the ball milling medium is added, the ball mill is started after the ball mill is sealed, and the mixing is carried out for 10 hours, and the powder to be fired is obtained by sieving.

[0130] 2) The powder to be fired is placed in a crucible for low-temperature firing; the low-temperature firing temperature is 1100°C, the firing time is 2 hours, and the powder is cooled with the furnace after firing. The heating and cooling rates are both 2°C / min to obtain BCZT ceramic particles containing T phase.

[0131] 3) Add cotton linters to a flask containing DMAC solution and soak for 48 hours. The mass ratio of cotton linters to DMAC solution is 1:30. After soaking, transfer to an oil bath-magnetic stirrer and stir at 160°C for 30 minutes. When the temperature in the flask drops to 80°C, take out the cotton linters, move the cotton linters to a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 100°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0132] 4) adding 2 g of the cotton linter cellulose obtained in step 3) to 60 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:10; stirring at 100° C. for 5 h, and then stirring at room temperature for 24 h, to obtain a regenerated cellulose casting precursor solution;

[0133] 5) The regenerated cellulose casting precursor solution is allowed to stand for 48 hours, and the impurities and the regenerated cellulose solution are separated at a centrifugal speed of 5000 r / min. After the centrifugation, the upper clear and transparent solution without impurities is collected to obtain the regenerated cellulose solution, which is sealed and stored.

[0134] 6) Add 2 g PVDF powder and 1.2 g LiCl to 18 g DMAC solution, with the mass ratio of LiCl to DMAC solution being 1:15, and stir at 50 °C for 2 h to obtain a PVDF casting precursor solution.

[0135] 7) The PVDF casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) were mixed at a mass ratio of 1:6, ultrasonicated for 30 minutes, stirred for 30 minutes, and repeated for 5 times, and finally transferred to a magnetic stirrer and stirred for 12 hours to obtain a regenerated cellulose / PVDF binary mixed casting precursor solution; 2wt% of T-phase BCZT was added to the regenerated cellulose / PVDF binary mixed casting precursor solution to obtain solution-4. After ultrasonication at room temperature for 1 hour, the solution was stirred at 70°C for 30 minutes to obtain a fourth regenerated cellulose / PVDF-BCZT ternary casting precursor solution.

[0136] 8) The fourth regenerated cellulose / PVDF-BCZT ternary casting precursor solution obtained in step 7) is injected into the guide plate of the adjustable scraper, the scraper height is adjusted to 25m, and the casting is carried out on a clean glass plate at a speed of 15cm / min. After completion, it is placed in a closed oven at a temperature of 25°C and dried for 12 hours. After complete drying, a layer of membrane-T is obtained.

[0137] 9) The film-T obtained in step 8) is moved together with the glass plate into an ice water bath and soaked for 60 minutes, and then the film is transferred to running tap water for 12 hours. The washed film is then transferred to an electric hot air drying oven and dried at 80°C for 8 hours, and a film-T is obtained after drying.

[0138] 10) Cut a circular film with a radius of 1.5 cm from the composite film in step 9), then cut out two copper electrodes with a radius of 1.2 cm, and then cut two wires with a length of 10 cm. Remove 1 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, and then stick them on the two copper electrodes, and then stick them on both sides of the circular film in a completely aligned manner. After the bonding is completed, a piezoelectric nanogenerator is obtained.

[0139] 11) Polydimethylsiloxane and diphenylbutyl carbamate were mixed and stirred at a mass ratio of 10:1 for 10 minutes, and the mixture was evacuated in a vacuum drying oven for 30 minutes to remove bubbles generated during stirring in the mixed solution. The vacuum degree was 0.8 MPa, and then a mixed solution for encapsulating a piezoelectric nanogenerator was obtained.

[0140] 12) Pour the mixed solution in step 11) into a 5cm×5cm×5cm clean container. After pouring the mixed solution to a height of 1mm, place a layer of membrane-T close to the surface of the liquid in the container and fix it. Then pour 1mm of the mixed solution into the container to cover the surface of the membrane. After that, put it in a closed drying oven and dry it at 80℃ for 2h to obtain the encapsulated piezoelectric nanogenerator-T.

[0141] Figure 1 Schematic diagrams of the structures of a layer of film -R prepared in comparative example 1 of the present invention, a layer of film -T prepared in comparative example 2 and a two-layer composite film -R / T prepared in embodiment 1; wherein, (a1) is a schematic diagram of a layer of film -R, and the white particles in the figure are added BCZT ceramic particles containing R phase; (a2) is a schematic diagram of a layer of film -T, and the black particles in the figure are added BCZT ceramic particles containing T phase; (a3) ​​is a schematic diagram of a two-layer composite film -R / T, and BCZT ceramic particles containing R phase and BCZT ceramic particles containing T phase are co-doped in the figure.

[0142] Figure 2 XRD refinement patterns of BCZT ceramic particles containing R phase and BCZT ceramic particles containing T phase prepared in Example 1 of the present invention; wherein, (a1) is BCZT ceramic particles containing R phase; the diffraction peak in the pattern corresponds to the R phase structure; (a2) is BCZT ceramic particles containing T phase; the diffraction peak in the pattern corresponds to the T phase structure.

[0143] Figure 3The short-circuit currents of different membranes measured in different modes; wherein, (a1) is a schematic diagram of the measurement of the piezoelectric nanogenerator in the d33 mode, showing the out-of-plane pressure; (a2) is a schematic diagram of the measurement of the piezoelectric nanogenerator in the d31 mode, showing the in-plane tension; (b1) is the output current of the piezoelectric nanogenerator-R prepared in comparative example 1 in the d31 mode; (b2) is the output current of the piezoelectric nanogenerator-R prepared in comparative example 1 in the d33 mode; the piezoelectric nanogenerator-R only generates a short-circuit current in the d31 mode, and almost no short-circuit current is generated in the d33 mode; (c1) is the output current of the piezoelectric nanogenerator-T prepared in comparative example 2 in the d31 mode The output current under the formula; (c2) is the output current of the piezoelectric nanogenerator-T prepared in comparative example 2 in d33 mode; the piezoelectric nanogenerator-T can only generate short-circuit current in d33 mode, and almost no short-circuit current is generated in d31 mode; (d1) is the output current of the paper-based piezoelectric nanogenerator-R / T prepared in Example 1 in d31 mode, (d2) is the output current of the paper-based piezoelectric nanogenerator-R / T prepared in Example 1 in d33 mode; the paper-based piezoelectric nanogenerator-R / T can generate short-circuit current in d31 mode and d33 mode, and can work and generate short-circuit current in two different modes. dij is the piezoelectric constant, which has two subscripts. The first subscript i represents the polarization direction of the crystal, denoted as i, i can be 1, 2 and 3; the second subscript j, j can be 1, 2, 3, 4, 5 and 6, indicating the direction of force on the material. The d31 mode and d33 mode are two common working vibration modes of piezoelectric vibration energy harvesters. Figure 3 In (a1), when the piezoelectric vibration energy harvester adopts the d33 working mode, the stress is in the j=3 direction. The piezoelectric material is subjected to the tensile stress applied by the outside in the j=3 direction. The mechanical deformation and electric field directions generated are both in the 3 direction, that is, the voltage and stress are in the 3 direction, which is called the d33 mode. Figure 3 In (a2), when the piezoelectric vibration energy harvester adopts the d31 working mode, the stress is in the direction marked by the black arrow, denoted as j=3. The piezoelectric material is subjected to compressive stress applied by the outside in the direction of the black arrow, and the mechanical deformation is also along the direction of the black arrow. However, the internal polarization of the film and the electric field generated are both in the horizontal direction, denoted as i=1, which is perpendicular to the direction indicated by the black arrow.

[0144] Figure 4The stress-strain curve and Young's modulus diagram of the one-layer film-R prepared in comparative example 1, the one-layer film-T prepared in comparative example 2, and the two-layer composite film-R / T prepared in example 1 under the same external force conditions; wherein, (a1) is the stress-strain curve diagram; (a2) is the Young's modulus diagram; it can be seen from the figure that the stress-strain tensile curve of the two-layer composite film-R / T is much higher than the curves of the one-layer film-R and the one-layer film-T, and the value of the Young's modulus of the two-layer composite film-R / T is also much higher than that of the one-layer film-R and the one-layer film-T, which shows that the three-dimensional hydrogen bond engineering constructed between the two-layer composite film-R / T has played a role, and many hydrogen bonds have been established in the three-dimensional hydrogen bond engineering between the two-layer film, which enhances the interaction force between the layers, and the composite structure of the two-layer film is more robust and not easy to be broken during the stress-strain tensile test. This enhancement of mechanical properties enables the piezoelectric nanogenerator to maintain a stable output during multiple multi-mode applications, improves the application scope and limit of the piezoelectric nanogenerator, and better meets the needs of society.

[0145] Table 1 Comparison of short-circuit current of paper-based piezoelectric nanogenerators prepared in Examples 1-4 and Comparative Examples 1-2

[0146]

[0147] Table 1 is a comparison of the short-circuit currents of the paper-based piezoelectric nanogenerators prepared in Examples 1-4 and Comparative Examples 1-2. It can be seen from the table that each example can detect the corresponding short-circuit current in two modes under the same test environment, among which, in the d31 mode, Example 1 has the largest short-circuit current, and in the d33 mode, Example 1 also has the largest short-circuit current. Overall, Example 1 has the largest short-circuit current and has the best performance.

[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a paper-based piezoelectric nanogenerator, characterized in that: The following steps are involved: 1) After the PVDF casting precursor solution and the regenerated cellulose solution are mixed and reacted, a regenerated cellulose / PVDF binary mixed casting precursor solution is obtained, which is divided into two equal parts, one part is added with BCZT ceramic particles containing R phase, and heated and stirred to obtain a first regenerated cellulose / PVDF-BCZT ternary casting precursor solution, and the other part is added with BCZT ceramic particles containing T phase, and heated and stirred to obtain a second regenerated cellulose / PVDF-BCZT ternary casting precursor solution; 2) Casting the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution, leaving it to stand, to obtain a semi-dried wet film as the first layer of the membrane, and then casting the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution on the basis of the semi-dried wet film to obtain a second layer of the membrane, and after drying, ice water bath immersion, rinsing, and secondary drying, a two-layer composite membrane is obtained; 3) After electrodes are attached to both sides of the two-layer composite film and connected with wires, the mixed solution is used for packaging to obtain a paper-based piezoelectric nanogenerator.

2. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the mass ratio of the PVDF casting precursor solution to the regenerated cellulose solution is 1:(5-7).

3. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the BCZT ceramic particles containing the R phase account for 1% of the mass of the regenerated cellulose / PVDF binary mixed casting precursor solution; the BCZT ceramic particles containing the T phase account for 1% of the mass of the regenerated cellulose / PVDF binary mixed casting precursor solution.

4. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the BCZT ceramic particles containing the R phase are prepared at a high temperature, wherein the high temperature is fired at a temperature of 1200-1300°C, the firing time is 1-3h, and the particles are cooled with the furnace after firing, with the heating and cooling rates being 2-5°C / min; the BCZT ceramic particles containing the T phase are prepared at a low temperature, wherein the low temperature is fired at a temperature of 1000-1200°C, the firing time is 1-3h, and the particles are cooled with the furnace after firing, with the heating and cooling rates being 2-5°C / min.

5. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the preparation method of the regenerated cellulose solution includes: adding cotton linters to a DMAC solution and soaking for 48-72 hours, wherein the mass ratio of cotton linters to DMAC solution is 1:(25-35), stirring at 160-180°C for 25-30 minutes, taking out the cotton linters when the temperature drops to 70-80°C, squeezing out the DMAC solution, transferring to an environment of 80-100°C for drying, and obtaining cotton linters cellulose; then adding the linters to a DMAC / LiCl mixed solution, stirring at 90-110°C for 3-5 hours, then stirring at room temperature for 24-30 hours, standing for not less than 48 hours, and centrifuging at a speed of 5000-5800 r / min to obtain a regenerated cellulose solution.

6. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the method for preparing the PVDF casting precursor solution includes: adding PVDF powder and LiCl to a DMAC solution, stirring at 50-70° C. for 2-3 hours, to obtain a PVDF casting precursor solution; the mass ratio of the PVDF powder, LiCl and DMAC solution is (1-3): (1-1.4): (15-20).

7. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 1), the mixing reaction conditions are: multiple ultrasonic stirring, and then continued stirring reaction; the time of continued stirring reaction is 10-12 hours; the heating stirring conditions are: heating stirring at 70-80°C for 30-50 minutes.

8. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 2), the casting conditions of the first regenerated cellulose / PVDF-BCZT ternary casting precursor solution are: casting on a glass plate at a speed of 12-15 cm / min to a thickness of 10-13 μm; the placement time is 6-8 hours; the casting conditions of the second regenerated cellulose / PVDF-BCZT ternary casting precursor solution are: casting on a semi-dried wet film at a speed of 12-15 cm / min to a thickness of 23-26 μm; The drying conditions are: drying at 25-30°C for 12-15 hours; the ice water bath soaking time is: 60-80 minutes; the rinsing conditions are: rinsing in running tap water for 12-15 hours; the secondary drying conditions are: secondary drying at 60-80°C for 6-8 hours.

9. The method for preparing a paper-based piezoelectric nanogenerator according to claim 1, characterized in that: In step 3), the mixed solution is obtained by mixing polydimethylsiloxane and a curing agent in a mass ratio of (9-11):1 and then vacuuming; the vacuuming conditions are: a vacuum degree of 0.8-1.0 MPa, and a vacuuming time of 20-30 min.

10. A paper-based piezoelectric nanogenerator, characterized in that: The paper-based piezoelectric nanogenerator is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of composite nanometer piezoelectric generator

    CN104157784A

  • Porous PVDF (Polyvinylidene Fluoride) composite material as well as nano generator and piezoelectric catalysis application thereof

    CN116218105A